2015
DOI: 10.1097/mao.0000000000000343
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Large Genomic Deletions Involving POU3F4 in Incomplete Partition Type III Inner Ear Anomaly in East Asian Populations and Implications for Genetic Counseling

Abstract: Our data suggest that different POU3F4 mutations might show different recurrence rate in siblings of the IP type III families, especially in East Asian population. Genetic counseling should be provided accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…The postoperative speech performance of IP type III subjects with the truncation or deletion mutation was found to be significantly poorer than that of controls. It has been previously reported that about 20% of DFNX2 subjects in Korea harbor a large genomic deletion involving POU3F4 . Although the mechanism responsible for the poorer performance of the truncation or deletion mutation cannot be clarified, realistic expectations can be provided to subjects with corresponding genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The postoperative speech performance of IP type III subjects with the truncation or deletion mutation was found to be significantly poorer than that of controls. It has been previously reported that about 20% of DFNX2 subjects in Korea harbor a large genomic deletion involving POU3F4 . Although the mechanism responsible for the poorer performance of the truncation or deletion mutation cannot be clarified, realistic expectations can be provided to subjects with corresponding genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that about 20% of DFNX2 subjects in Korea harbor a large genomic deletion involving POU3F4. 11 Although the mechanism responsible for the poorer performance of the truncation or deletion mutation cannot be clarified, realistic expectations can be provided to subjects with corresponding genotypes. This is the first study to address the possible effects of POU3F4 genotypes on CI results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Last but not the least, DFNX3 has already been diagnosed in molecular level, so POU3F4 gene should be screened in the outpatient persons who have the clinical phenotypes of DFNX3. [272829] Our study also has some limitations. On one hand, more pedigree and sporadic people should be recruited.…”
Section: Discussionmentioning
confidence: 97%